Studi Pengunaan Pakan Pelet Hasil Formulasi dari Bahan Baku Nabati Untuk Meningkatkan Pertumbuhan Benih Ikan Gurami (Osphronemusgouramy) - Munawar Khalil; Zahnila Zahnila; Prama Hartami (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
The study aimed to determine the effect of formulated feed from different vegetable sources onto growth of gouramy fingerling (Osphronemus gouramy). The method used a non factorial completely randomized design with five treatments and three replications, namely A: commercial feed (control), B: formulated feed of Moringa, C: formulated feed Gliricidia, D: formulated feed ofCentella asiatica and E: formulated feed of three vegetable mixture. The results showed that formulated feed from different vegetable sources gave highly significant effect on growth of length (1,025± 0,126 cm in average) and weight1,133 ± 0,212 gram in average), feed conversion ratio (6,96±0,32 in average)and the response of fish to feed (25,61±0,65 minutes), which was Fcount > F table. The highest value on growth and feed conversion ratio was obtained in treatment B, whereas, the best response of fish to formulated feedwas obtained in treatment A (commercial feed). Furthemore, formulated feed also provided survival rate of gouramy (Osphronemus gouramy) relatively well.